The effect of Y, Ce and Gd on texture, recrystallization and mechanical property of Mg–Zn alloys - Peng Liu; Haitao Jiang; Zhengxu Cai; Qiang Kang; Yun Zhang (Journal of Magnesium and Alloys, 2016)
The effect of Gd, Ce and Y elements on texture, recrystallization and mechanical properties of Mg–1.5Zn alloys was investigated. The results show that the addition of Gd, Ce and Y elements in Mg–1.5Zn alloy, which rolled at 450 °C and subsequently annealed at 350 °C for 1h, can effectively weaken and modify the basal texture, characterized by the splitting basal pole toward to transverse direction, leading to the yield and tensile strength, the highest along the rolling direction and the lowest along the transverse direction. Besides, the unique basal texture contributes to the significant improvement of elongation at room temperature. Electron back scattering diffraction (EBSD) analysis indicated that the non-basal texture in Mg–1.5Zn–0.2RE alloys can be attributed to obstructive effect of static recrystallization and the non-basal orientation grains nucleation near pre-existing grain boundaries during annealing. Specially, the Mg–1.5Zn–0.2Gd sheet exhibits much excellent plasticity with the elongation of 27% than Mg–1.5Zn–0.2Ce and Mg–1.5Zn–0.2Y alloys, resulting from the less and smaller second phase of MgZnGd.